(Patho-)Physiology of Na+/H+ Exchangers (NHEs) in the Digestive System - Cao, Li; Yuan, Zhenglin; Liu, Mei; Stock, Christian (Frontiers in Physiology, 2020)
Na+/H+ exchangers (NHEs) are expressed in virtually all human tissues and organs. Two major tasks of those NHE isoforms that are located in plasma membranes are cell volume control by Na+-uptake and cellular pH regulation by H+-extrusion. Several NHEs, particularly NHE 1-4 and 8, are involved in the pathogenesis of diseases of the digestive system such as inflammatory bowel disease (ulcerative colitis, Crohn’s disease) and gastric and colorectal tumorigenesis. In the present review, we describe the physiological purposes, possible malfunctions and pathophysiological effects of the different NHE isoforms along the alimentary canal from esophagus to colon, including pancreas, liver and gallbladder. Particular attention is paid to the functions of NHEs in injury repair and to the role of NHE1 in Barrett’s esophagus. The impact of NHEs on gut microbiota and intestinal mucosal integrity is also dealt with. As the hitherto existing findings are not always consistent, sometimes even controversial, they are compared and critically discussed.